2000
DOI: 10.1038/modpathol.3880230
|View full text |Cite|
|
Sign up to set email alerts
|

Malignant Peripheral Nerve Sheath Tumors with t(X;18). A Pathologic and Molecular Genetic Study

Abstract: Spindle cell sarcomas often present the surgical pathologist with a considerable diagnostic challenge. Malignant peripheral nerve sheath tumor, leiomyosarcoma, fibrosarcoma, and monophasic synovial sarcoma may all appear similar histologically. The application of ancillary diagnostic modalities, such as immunohistochemistry and electron microscopy, may be helpful in the differentiation of these tumors, but in cases in which these adjunctive techniques fail to demonstrate any more definitive evidence of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
0
40
2
Order By: Relevance
“…The SYT-SSX fusion transcript is specific for a diagnosis of SS and is generally not identified in any other sarcoma 23 except for occasional reports of its detection in malignant peripheral nerve sheath tumor. 24,25 As part of a larger study on malignant small round cell tumors, we have performed RT-PCR for the SYT-SSX fusion transcript in 25 cases of Ewing sarcoma and 12 cases of rhabdomyosarcoma, all of which were negative for this transcript.…”
Section: Discussionmentioning
confidence: 99%
“…The SYT-SSX fusion transcript is specific for a diagnosis of SS and is generally not identified in any other sarcoma 23 except for occasional reports of its detection in malignant peripheral nerve sheath tumor. 24,25 As part of a larger study on malignant small round cell tumors, we have performed RT-PCR for the SYT-SSX fusion transcript in 25 cases of Ewing sarcoma and 12 cases of rhabdomyosarcoma, all of which were negative for this transcript.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Malignant peripheral nerve sheath tumor can be particularly difficult to distinguish from synovial sarcoma, as they share several morphological, immunohistochemical and ultrastructural features. [13][14][15] Some authors have even reported the rare occurrence of a t(X;18) translocation in malignant peripheral nerve sheath tumor, 16 adding further difficulty in differentiating these two tumors. Thus, markers specifically expressed in either one tumor or the other would be extremely useful.…”
mentioning
confidence: 99%
“…t(X;18) (SYT-SSX) fusion gene transcripts were observed in 83 of 86 synovial sarcomas (96% sensitivity) and never detected in any of the 135 tumors of other type that had been examined (100% specificity). Using the same technique on the same kind of material, O'Sullivan et al (5) found (SYT-SSX) fusion gene transcripts in 29 of 34 (85%) synovial sarcomas, but also in 15 of 20 (75%) MPNSTs, 1 of 4 adult fibrosarcomas, 1 of 10 malignant fibrous histiocytomas, 1 of 7 congenital-infantile fibrosarcomas, and 2 of 3 neurofibromas. Based on these results, the authors concluded that the translocation t(X;18) is not specific for synovial sarcoma and, thus, should be used with great caution in the differential diagnosis of spindle cell tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, O'Sullivan et al (5) did not try to confirm their unexpected and provocative results with techniques other than RT-PCR such as in situ hybridization, which could have been applied on paraffin-embedded material as well. They did not ask another independent laboratory to verify their results on the same samples either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation